Analisis Data Pemahaman Anggota Komunitas Japan Club 6 Garut Tentang Bahaya dan Dampak Dari Ujaran Kebencian - Satria, Eri; Hakim, Arif L; Hawari, Ciptaraka N; Azwardhi, Miftah Y; Faturrahman, Muhamad; Rahman, Taupik (Journal of Digital Literacy and Volunteering, 2023)
Hate speech is a behavior that based on hatred to some tribes, religions, races, ethnic, skin color, believes, or faiths, Hate speech could be a worst impact to individual or social human beings and can be founded in various media. So in that case, social community must be given knowledge aboout impact and dangerous of hate speech. IT volunteers provides educational presentation to anticipating the impact and dangerous of hate speech for partnership that has been cooperated with IT volunteers. The community that has been appertain to do partnership is the community that have interest in culture and technology in focus to country of Japan, this community centered in SMAN 6 Garut highschool that called by Japan Club. For making sure that the educational presentation of the dangerous and impact of hate speech has been delivered successfully to the community, IT volunteers provides a socialitation with different session and a test. Then, statistical hypothesis test conducted by the IT volunteers on purpose for measuring the community knowledge after the socialitation done by every respondent that present in that presentation done by IT volunteers. In conclusion, that result of the dangerous and impact of hate speech presentation has been succesfully understood by the object.